Kinerja Keuangan dan Efisiensi Operasional Perusahaan Proper Peringkat Lebih dari Taat dalam Pengelolaan Lingkungan Hidup - Saraswati Ratmayanti, Nyoman Gita; Agung Suaryana, I Gst Ngurah (E-Jurnal Akuntansi; Vol 31 No 1 (2021), 2021)
The object of this study is the financial performance and operational efficiency of the PROPER company with data one year before and after achieving a rating that is more than obedient or achieving a green or gold rating. The analysis technique used was the T-Paired test to determine differences in average financial performance, and operational efficiency before and after achieving the Green Proper rank. The results of the research show that companies that have received the Green Proper rank, which have a high commitment to obedience and care for environmental management, there is no difference in the improvement of financial performance seen from ROS, ROA and ROE. The Green Proper company has not been able to improve its operational efficiency through the Net Income Efficiency (NIEFF), which is the contribution per worker to the company's profit. The Sales Efficiency (SALEFF) shows insignificant results. Keywords: F inancial Performance; Operational Efficiency.